Pengaruh Suhu, Hujan dan Kelembaban Terhadap Kerusakan Jalan di Kabupaten Pacitan - Diana Rendrarini (LPPM Universitas Merdeka Madiun, 2019)
Indonesia as a tropical country has two seasons, namely the dry season and the rainy season. Each season changes usually have a significant influence in several regions. Pacitan Regency is an area in East Java, part of which is the coast and mountains. Several roads in Pacitan Regency have damaged conditions, including waterlogging, potholes and bumpy conditions. Some factors that cause damaged road conditions include the influence of temperature, rain, and humidity. In this study data analysis was performed using Multiple Linear Regression analysis with the Stepwise method. Where this research is quantitative and ex-post facto research. The data collection method uses the documentation method, which is collecting secondary data from several related agencies. Based on the results of data analysis using Multiple Linear Regression Analysis with the Stepwise method, it can be concluded that the temperature factor has an influence on road damage, while the rain and humidity factors do not have any effect.